Association between the quality of inner cell mass and first trimester miscarriage after single blastocyst transfer - Dayuan Shi; Jiawei Xu; Meixiang Zhang; Wenbin Niu; Hao Shi; Guidong Yao; Ying Li; Nan Zhang; Yingpu Sun (BMC, 2020)
Abstract Background The blastocyst morphology provided valuable roles for predicting pregnancy and live birth, but was still not fully understood for evaluating miscarriage. The aim of this study was to explore the association between blastocyst morphologic evaluation and first trimester miscarriage combined with karyotype of miscarried conceptus. Methods This retrospective cohort study included a total of 2873 clinical pregnancy cycles with single blastocyst transfer performed from January 2013 to April 2019. Chromosome karyotype of miscarried conceptus was analyzed via single nucleotide polymorphism array analysis. Miscarriage and karyotype of miscarried conceptus associated with blastocyst morphology were analyzed by chi-square and logistic regression analysis. Results A total of 354 (12.3%) cycles resulted in first trimester miscarriage. Miscarriage rates increased with trophectoderm (TE) grade from A to C (P = 0.012), while three morphologic parameters (blastocoele expansion degree, inner cell mass (ICM) and TE) showed no statistical significance with miscarriage after multivariable analysis. The rate of aneuploidy was 47.7% (83 of 174) in total miscarried conceptuses. For euploid miscarriages, the grade B of ICM occupied a higher proportion compared with aneuploidy, with OR of 2.474, (95% CI, 1.311-4.699), P = 0.005. Conclusions Chromosomal aberration of embryo is an important genetic factor for first trimester miscarriage, and the quality of ICM is a potential indicator for euploid miscarriage. Blastocysts with grade A of ICM should be given priority during single blastocyst transfer to reduce potential miscarriage.